RESPONSIBILITY OF RELIGIOUS EDUCATION TEACHER IN IMPLEMENTATION OF CHRIST’S PERSONALITY INTO STUDENTS - Bangun Munte (Jurnal Dinamika Pendidikan, 2020)
This research intends to see of to what extend is the responsibility of religious education teacher in implementation of Christ’ personal into students themselves at grade XII of PMIA SMA Negeri 2 Pematangsiantar at academic year 2019/2020. The number of subjects is sixty students. This research applies descriptive method, while data analysis which is done in this hypothesis is product moment correlation of Pearson. The instrument which is used to collect the data is questionnaires for variable X (Responsibility of religious education teacher) and Variable Y (Christ’s personality belonged to the students). To know the extent of religious education teacher in implementation of Christ’s personality into students themselves, statistic test of correlation product moment Pearson is used. The test result show correlation ®0,5068 with determination test is 25,68% and to know whether significant or not correlation at the real level = 0,05 so “t”test is done with the criteria of testing if tcount which is gained greater than (>) from ttabel at the significant level of 1 – 0,05 with dk = n – 2 so hypothesisis accepted and in other side is rejected. From the result of testing is gained tcount > ttable ( 4,59 > 1,67 ), so hypothesis is accepted. This condition can be concluded that religious education teacher has responsibility in implementation of Christ’s personality into studntes themselves at Grade XII PMIA of SMA Negeri 2 Pematangsiantar at academic 2019/2020. Keywords: Religious education teacher, implementation of Christ’ personality